Detection of X-Chromosome Inversions in Anopheles Pharoensis Collected from Egypt and Sudan by PCR Assay: Life Sciences -Biology - Nasir, Najlaa Siddig; Fadul Ali, Fatima; M. Mohamed, Fatima; Elamin, Mohamed Osman; M. Alshehri, Ali; M. Badri, Hatim; A. Natto, Hatim; Alfaifi, Mashael; A. Osman, Ahmed (International Journal of Life Science and Pharma Research, 2023)
Globally, the WHO estimated 241 million malaria cases with 627000 deaths in Africa in 2020. Studying inversions in the X-chromosomes could detect behavioral changes and efficiency of transmission of Malaria in Anopheles phronesis species. These changes may lead to shifting from becoming a major vector of Malaria after the inability to transmit Malaria. The knowledge of the malaria transmission pattern of Anopheles pharoensis in Sudan needs to be improved. We aimed to detect the presence of any inversions or mutations in Anopheles pharoensis species collected from Egypt and Sudan and to undergo a Polymerase Chain Reaction (PCR) technique to detect mutations or X-chromosome inversions in the Sudanese and Egyptian strains of Anopheles pharoensis also to compare between the X-chromosome of the two species. It is an experimental, analytical study that aimed to detect inversions in the X –chromosomes of Anopheles phronesis collected from Egypt (Faiyoum Governate) and Sudan (Khartoum, Gezira, and Sennar states) of Sudanese Mosquito species. From the gel electrophoresis and PCR assay, inversions were detected by the 100Bp PCR products using primers. Only very few revealed bands from 75 Egyptian strains were detected by bands. The study revealed that Anopheles pharoensis species collected from Egypt have X- chromosome inversions. Inversions were absent in the Sudanese strains. The study also reacted to the fact that Anopheles phronesis could be a sibling species or a species complex, but further studies are needed to prove this. From the results and observations of this investigation, it was recommended to undergo further genetic studies on Anopheles species in Sudan and use of PCR technique in the classification.